Population and Economic Growth: A Review Essay - Marinko Škare; Sanja Blažević (Amfiteatru Economic Journal, 2015)
For centuries, scientists from various scientific fields have been leading lively discussions on the (bidirectional) relationship between population growth and economic growth. Particular attention was given to the nature of the population growth variable, i.e. whether it is an endogenous or exogenous variable. The goal of this paper is to position this discussion into a historical, empirical and institutional perspective in order to establish population as an important factor for socio-economic prosperity, mostly measured in terms of economic growth. Regardless of ambiguous empirical conclusions about the influence of population growth on economic growth, the political aspect is crucial. Population effect should not be measured only in terms of population growth, measured by the increase in the number of inhabitants. Population is an endogenous variable which is under the influence of culture, values, political processes and industrial structure.
Keywords: Q56; J13; J18; L38; 330; population; economic growth; United Nations; fertility; policy